The influence of vibratory massage after physical exertion on selected psychological processes - Wrześniewski, Krzysztof; Pałka, Tomasz; Blecharz, Jan (Frontiers in Psychology, 2024)
Good mental preparation of an athlete plays an important role in achieving optimal sports results. An athlete who enters a competition should not feel fatigue resulting from intense physical exercise (Armstrong et. al., 2022). Therefore, new and effective methods are being sought that could help accelerate the process of both physical and mental regeneration. Vibrotherapy is one of them (Uher, 2018). The aim of the study was to determine the optimal frequency of vibration, its duration and the position in which the subjects were placed during the treatments, in relation to the reduction of subjectively perceived exertion muscle pain, mental discomfort, emotional states and the level of cognitive processes that were disturbed by intense physical activity. Sixteen healthy male volunteers were involved in this study. The participants were assessed for their aerobic and anaerobic capacity. Each of the subjects performed a set of intensive physical exercises and then underwent vibrotherapy treatment. In random order, each of the men tested the effectiveness of eight combinations of frequency, duration, and body position. Psychological tests were conducted for each combination: frequency, duration of treatment, and position during treatment, in four stages: 1) before the start of the experiment (baseline POMS measurements), 2) immediately after the exercise (VAS scale, pain and psychological discomfort and STROOP test), 3) immediately after the vibration treatment (POMS measurements, VAS VAS scale: pain and psychological discomfort and STROOP test), 4) 24 hours after the vibration treatment (VAS scale: pain and psychological discomfort). Based on the results, it was concluded that all the studied variables improved significantly over time (after the vibration treatment and 24 hours after training). In addition, a statistically significant interaction measurement × frequency was noted for vigor scale (52HZ favored greater improvement in this state), and a statistically significant interaction was found for measurement × time for the VAS scale (p<0.05) -the lower pain value was indicated 24 hours after the 10-minute vibration treatment. The type of frequency used, position, and duration of the treatment did not play a statistically significant role in changing STROOP test results and severity of psychological discomfort (p>0.05).